Transport Safety for Agricultural Equipment on Utah’s Public Thoroughfares - Beard, F.R.; Miller, B.E.; Darcey, C.L.; Joerger, R.M. (Journal of Agricultural Systems, Technology, and Management, 2000)
Utah’s earlier pilot/escort legislation and certification program did not address the unique nature of implements of husbandry. Agricultural equipment dealers, the Mountain States Association, and Utah State University Extension combined efforts to have these laws changed. Working in conjunction with the Utah Department of Agriculture, commercial transport regulations were enacted which addressed agricultural tractors, self-propelled equipment and agricultural implements. Concurrently, students majoring in Agricultural Machinery Technology at Utah State University, developed and marketed a set of safety equipment which was recognized by the State as satisfying all requirements for the safe transport of implements of husbandry on Utah’s public thoroughfares.